Electrophysiological Properties of Subventricular Zone Cells in Adult Mouse Brain - Lai, Bin (2010)
The subventricular zone (SVZ) is a principal site of adult neurogenesis and appears to participate in the brain’s response to injury. Thus, measures that enhance SVZ neurogenesis may have a role in treatment of neurological disease. To better characterize SVZ cells and identify potential targets for therapeutic intervention, we studied electrophysiological properties of SVZ cells in adult mouse brain slices using patch-clamp techniques. Electrophysiology was correlated with immunohistochemical phenotype by injecting cells with lucifer yellow and by studying transgenic mice carrying green fluorescent protein under control of the doublecortin (DCX) or glial fibrillary acidic protein (GFAP) promoter. We identified five types of cells in the adult mouse SVZ: type 1 cells, with 4-aminopyridine (4-AP)/tetraethylammonium (TEA)-sensitive and CdCl(2)-sensitive inward currents; type 2 cells, with Ca(2+)-sensitive K(+) and both 4-AP/TEA-sensitive and -insensitive currents; type 3 cells, with 4-AP/TEA-sensitive and -insensitive and small Na(+) currents; type 4 cells, with slowly activating, large linear outward current and sustained outward current without fast-inactivating component; and type 5 cells, with a large outward rectifying current with a fast inactivating component. Type 2 and 3 cells expressed DCX, types 4 and 5 cells expressed GFAP, and type 1 cells expressed neither. We propose that SVZ neurogenesis involves a progression of electrophysiological cell phenotypes from types 4 and 5 cells (astrocytes) to type 1 cells (neuronal progenitors) to types 2 and 3 cells (nascent neurons), and that drugs acting on. ion channels expressed during neurogenesis might promote therapeutic neurogenesis in the injured brain.